E-Satisfaction as a Mediator Between E-Service Quality, E-Trust, and E-Loyalty - Florence, Jessica; Aprillia, Ariesya (APTISI Transactions on Management (ATM), 2025)
The rapid growth of online commerce has dramatically altered consumer be- havior, highlighting the crucial role of high-quality digital services and customer trust in establishing lasting customer loyalty. Nevertheless, the mediating effect of e-satisfaction on the relationship between e-service quality, e-trust, and e- loyalty still requires deeper exploration. The current research aims to analyze the mediating role of e-satisfaction in the relationship between e-service quality and e-trust toward e-loyalty among consumers engaging in online shopping activities in the Greater Bandung region. The study collected data from 302 re- spondents through an online survey conducted using Google Forms, distributed via WhatsApp and Instagram. The research employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the seven formulated hypothe- ses. Findings indicate that e-service quality significantly affects e-satisfaction, while e-trust also exhibits a direct positive effect on e-satisfaction. Addition- ally, both e-service quality and e-trust positively contribute to e-loyalty, with e-satisfaction playing a significant role in enhancing e-loyalty. The study further identifies e-satisfaction as a mediator between e-service quality and e-loyalty but not between e-trust and e-loyalty. These results underline the importance of high-quality service and trust in driving customer retention within online busi- ness environments. Consequently, online business platforms are encouraged to focus on enhancing user experiences by delivering secure, efficient, and superior quality services to foster stronger customer connections and promote enduring loyalty.